2022
DOI: 10.3390/electronics11060888
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Physiological Signals for Stress Recognition with Different Car Handling Setups

Abstract: When designing a car, the vehicle dynamics and handling are important aspects, as they can satisfy a purpose in professional racing, as well as contributing to driving pleasure and safety, real and perceived, in regular drivers. In this paper, we focus on the assessment of the emotional response in drivers while they are driving on a track with different car handling setups. The experiments were performed using a dynamic professional simulator prearranged with different car setups. We recorded various physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In this study, we aimed to explore the benefits of sensor fusion by synchronizing multiple developed biosensors on the same BSN and implementing DL algorithms with multiple sensor fusion approaches. In previous works, we assessed the emotional states of drivers using machine learning approaches with either SPR signals only [54,55] or a combination of SPR and ECG signals [56][57][58]. In this work, we focused on evaluating the level of drivers' mental engagement during manual and autonomous driving scenarios by employing advanced DL models that integrate EEG, SPR, and ECG signals.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aimed to explore the benefits of sensor fusion by synchronizing multiple developed biosensors on the same BSN and implementing DL algorithms with multiple sensor fusion approaches. In previous works, we assessed the emotional states of drivers using machine learning approaches with either SPR signals only [54,55] or a combination of SPR and ECG signals [56][57][58]. In this work, we focused on evaluating the level of drivers' mental engagement during manual and autonomous driving scenarios by employing advanced DL models that integrate EEG, SPR, and ECG signals.…”
Section: Discussionmentioning
confidence: 99%
“…A novel paradigm for collecting physiological data in multi-sensory emotion detection was proposed by Asiain et al [21]. In order to aid in the identi cation of stress, Zontone et al [22] created a technique to gauge drivers' emotional reactions in a variety of driving situations. In order to evaluate car interior acceleration noises in conjunction with physiological inputs and produce precise sound quality judgements, Xie et al [23] created a hybrid deep neural network.…”
Section: Literature Surveymentioning
confidence: 99%
“…Asiain et al [21] proposed a novel platform of physiological signal acquisition for multi-sensory emotion detection to record and analyze different physiological signals, and the most important features of the proposed platform were compared with those of a proven wearable device. Zontone et al [22] built a system to assess the emotional response in drivers while they were driving on a track with different car handling setups. The experimental results based on the system indicated that the base car setup appeared to be the least stressful, and that the presented system enabled one to effectively recognize stress while the subjects were driving in the different car configurations.…”
Section: Introductionmentioning
confidence: 99%